Epidemiology of Sapovirus Infections in a Birth Cohort in Peru - Sánchez G.J. (2018)
Sapovirus is one of the primary viral causes of acute gastroenteritis (AGE), especially where rotavirus vaccination has been implemented. The characteristics and impact of natural infection at the community level, however, have not been well documented.